Chemical Chaos - Arnold, Nick (Horrible Science, 2008)
Science with the squishy bits left in! Why aren't glass eyes really made of glass? What would make the worst stink bomb ever? How do you make your own toothpaste? Get the awful answers in Chemical Chaos!